Options for correcting nephrogenic anemia in a patient with HIV and chronic kidney disease. Case report - Victor V. Fomin (Consilium Medicum, 2024)
Anemia is a distinctive manifestation of chronic kidney disease (CKD); it occurs already from stage III CKD and is observed in the vast majority of patients with end-stage renal disease. The primary mechanism of renal anemia is a decrease in the production of endogenous erythropoietin; deficiency conditions, chronic inflammation, and hyperparathyroidism also play an essential role in pathogenesis. The main therapy for anemia in CKD is erythropoiesis-stimulating agents (ESAs), which are divided into short-acting and long-acting. In patients with end-stage renal disease on hemodialysis, the preferred treatment for anemia is erythropoietin alpha. However, in some cases, ESA resistance develops, which complicates treatment. One of the reasons for the emergence of ESA resistance is the inflammatory process. The article presents a clinical case of a patient with HIV type 1, hepatitis C infection, and ESRD requiring long term hemodialysis, severe anemia, and resistance to current therapy.